Pharmacological treatment of obesity: an overview of different groups of anti-obesity drugs available in Poland - Woch, Barbara; Bereza, Dawid; Sokołowska, Katarzyna; Kulak, Maria; Moreau, Igor; Polańska, Paulina; Lang, Miriam (Journal of Education, Health and Sport, 2024)
Introduction and Objective: Obesity, as one of the diseases of civilization, has become a significant problem in our time. Although the first ways of treating it appeared many years ago, pharmacotherapy of obesity has been developing significantly in recent years. The purpose of this article is to introduce the obesity drugs that have been registered for the treatment of obesity in Poland and to describe a new substance called tirzepatide, which, although it does not have such registration yet, is one of the most promising medications of the near future. State of Knowledge: Obesity is an urgent and growing problem. In Poland, about 25% of adults are obese, and this number is increasing over the years. In Europe, four drugs belonging to three different groups are registered for the treatment of obesity: orlistat, a combined drug that includes naltrexone hydrochloride and bupropion hydrochloride, liraglutide, and semaglutide. Although the last drug achieves the best results in studies and is the substance most favored by doctors and patients, there is still much research on new substances and formulations, which would bring even better results and health benefits. One of these substances is tirzepatide, a drug registered in 2022 for the treatment of type 2 diabetes. Summary: Nowadays in Poland, there are four drugs registered for obesity. Two of them are representatives of the group of GLP-1 analogues. Pharmacological treatment of obesity has good results and is a relatively safe process that should be implemented in conjunction with lifestyle changes. The fifth substance described in this article is tirzepatide, a drug that, although not registered for the treatment of obesity yet, is for now one of the most promising substances among the new drugs.